Lunch break - Manuel Echavarria::::::photographer:::
Paulino Pacheco, far right, and Cesar Chavez, middle left, take a lunch break at Preisker Park after a march and rally while local supporters look on. Paulino Pacheco, el primero en la derecha, y Cesar Chávez, el de en medio a la izquierda, almuerzan en el Parque Preisker después de desfilar y hacer su demostración, mientras simpatizantes locales observan